Experience-centred foreign language acquisition in early childhood (Training and Practice : Journal of Educational Sciences, 2020)
In our study, we would like to present the principles of communication and the experience-centred foreign language acquisition in early childhood. The result of teaching a second language depends mainly on the personality of the teacher, on emotional factors and on the teaching methods. During one’s studies, the experience centred process is the most important factor which can be realized in the topics discussed during the kindergarten year. Playing is the main activity of children: through role-play they develop their language skills since they can experience everyday real-life situations. We integrate this approach into the theoretical training of the bilingual kindergarten teachers, and they also use this technique during their professional practical training. In our study, we want to present how the above-mentioned methods can be realized during practice.